Madrasah Head's Strategy In Improving Students' Academic Achievement - Bustanul Arifin; Ahmad Thoyyib Mas’udi (Pascasarjana Universitas Qomaruddin, 2024)
School principal strategies can enhance the performance of educators in the learning process. In his role as a leader, the principal implements various strategies to increase student achievement as a benchmark for the success of school management. As a leader, the principal plays the role of educator, manager, administrator, supervisor, inspirer, innovator, and motivator. This research aims to explore the strategies implemented by the Head of Madrasah in improving student academic achievement at MTs Al Hidayah Wedoro Glagah Lamongan, as well as identify supporting and inhibiting factors in implementing these strategies. The madrasah principal plays a central role as a leader who is responsible for directing and managing various aspects of education, including his role as educator, manager, administrator, supervisor, inspirer, innovator, and motivator. This research employs a qualitative descriptive approach, utilizing field research methods. We collected data through semi-structured interviews with madrasa heads, teachers, and support staff, as well as through participant observation and the collection of related documents. The data analysis process involves data reduction, data presentation, and drawing conclusions, with data validity tested using triangulation techniques to ensure the accuracy of the results. Research findings reveal that madrasah principals have implemented various strategies to improve students' academic achievement. These strategies include adjusting the curriculum for better relevance, developing teacher competency through training and workshops, improving learning facilities and resources, as well as collaborating with external tutors and other educational institutions. Madrasah heads also implement continuous evaluation and monitoring to assess the effectiveness of the strategies implemented and to identify areas that need improvement. The focus of teacher competency development is on enhancing pedagogical skills and utilizing educational technology effectively. Improvements to facilities include the provision of computer laboratories, better libraries, and access to digital resources to support a more modern learning process.